Analysis of Process Parameters in Surface Grinding Process. (2018) - Saravanakumar, A.; Dhanabal, S.; Jayanand, E.; Logeshwaran, P.
Abstract: Surface grinding is a familiar method used in the division of manufacturing in order to generate smooth finish on flat surface. Surface finish and metal removal rate are the two major characteristics to be considered in the grinding process. In this paper, Taguchi method L18-OA of design of experiments is used to analyse the grinding process parameters such as grinding wheel speed, table speed & depth of cut in order to get superior surface finish. The depth of cut, table speed and wheel speed are used to find dominant factor affecting surface finish and metal removal rate of the grinding process.